Primera cita en España del eriófido de la alcachofa Aceria neocynarae (Keifer) - González Néñez, M.=700 1 Budia, F.; Viñuela, E.; Esteban Durán, J. R.; Adán, A.; Medina, P.; Scheneider, M. I.; Del Estal, P.
Resumenes (Es, En)
7 fig; 5 ref.
Keywords: ACERIA; ERIOPHYIDAE; ACAROS ERIOFIDOS; HUESPEDES ALTERNATIVOS; ALCACHOFA; ACERIA NEOCYNARAE